Rancang Bangun Sistem Informasi Penjualan Fashion Berbasis Web - Budi Sudradjat (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2018)
Sales System at H2H Couple Fashion today still use manual and very simple. Buyers must come directly so as not effective and efficient. Means of promotion there is inadequate so poorly known, it is harder to obtain for potential buyers. With the establishment of an online sales system web-based is expected to provide ease of transaction as well as a means of effective and efficient promotion with a wide range of markets and provide satisfaction to customers thereby increasing profits for the company. Design, code creation, testing and support. by using a modeling tool such as a unified Modeling Language (UML), Entity Relationship Diagram (ERD) and data collection techniques by observation, and interviews. While the database application development tools using MySQL and PHPMyAdmin and PHP programming language, Adobe Dreamweaver CS6 text editor. This application provides product information and generate reports including product reports and sales reports.